Gamification Design in Online Risk Management to Enhance Employee Awareness - Muhamad Dody Firmansyah; Jonathan Jonathan; Tony Wibowo (Jurnal Sisfokom (Sistem Informasi dan Komputer), 2026)
Organizations increasingly require effective approaches to strengthen employee awareness of operational risks, yet conventional training methods often lack engagement and fail to support sustained learning. This study aimed to design and evaluate a gamified risk-management learning prototype that integrates interactive features with structured instructional content. The research focused on early-stage development and formative evaluation because existing workplace learning research has not sufficiently explored the feasibility of gamification in risk-related training. The study employed the first three stages of the 4D R&D model: Define, Design, and Develop to create the prototype, followed by a descriptive quantitative evaluation involving 82 participants. Data were collected using an online questionnaire adapted from validated instruments measuring usability, content clarity, interactivity, and user satisfaction. The results showed consistently high mean scores across all constructs, indicating positive user perceptions of the prototype’s interface, clarity of information, and engagement generated by gamified elements. Cronbach’s Alpha (0.985) confirmed excellent internal consistency, and correlation analysis demonstrated strong relationships among clarity, interactivity, and satisfaction. Overall, the findings suggest that gamification can serve as a feasible and engaging approach for risk-management learning in organizational contexts. The study provides early empirical evidence supporting further refinement, broader implementation, and more extensive testing of gamified learning systems for workplace risk awareness.